Bilateral fibroadenoma of the ectopic breast tissue in axilla: A case report - Bharani Rajkumar; Sasivannan Anbarasu; Lavanya Rajagopal (Universiti Kebangsaan Malaysia, 2015)
Anomalies associated with breast development are common, presenting as supernumerary nipples (polythelia) and less often as supernumerary breast (polymastia) in 1–5% of population. These anomalies are more common in women and also most frequently located along the mammary line, extending from the axilla to pubic region. The axillary polymastia is the most common variant of ectopic breast tissue (EBT). EBTcan undergo the same physiological and pathological processes as the normal breast. The incidence of fibroadenoma developing in ectopic breast is a rare entity, most common being the carcinoma. We report here a case of fibroadenoma of EBT in both axillae of a 33-year-old Asian woman. This case has been reported for its rarity and to reemphasize the importance of screening of EBT for any pathology during routine screening of breast.